2002
DOI: 10.1128/aem.68.12.6182-6192.2002
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness of Chromosomal and Plasmid DNAs of Erwinia pyrifoliae and Erwinia amylovora

Abstract: The plant pathogen Erwinia pyrifoliae has been classified as a separate species from Erwinia amylovora based in part on differences in molecular properties. In this study, these and other molecular properties were examined for E. pyrifoliae and for additional strains of E. amylovora, including strains from brambles (Rubus spp.). The nucleotide composition of the internal transcribed spacer (ITS) region was determined for six of the seven 16S-23S rRNA operons detected in these species with a 16S rRNA gene probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 43 publications
2
61
0
6
Order By: Relevance
“…Genomic sequence comparison using EDGAR (1) revealed approximately 373 singletons from ATCC BAA-2158 that were absent or highly divergent in the genomes of Spiraeoideaeinfecting strains CFPB 1430 and ATCC 49946 of E. amylovora (10,12). However, genomic sequence comparison of ATCC BAA-2158 with these strains of E. amylovora and the closely related species E. pyrifoliae DSM 12163 T (11), E. tasmaniensis Et1/99 (5), and E. billingiae Eb661 (4) corroborates other analyses (e.g., DNA-DNA hybridization and sequencing of housekeeping genes) that retain ATCC BAA-2158 within the species E. amylovora (3,7).…”
supporting
confidence: 67%
“…Genomic sequence comparison using EDGAR (1) revealed approximately 373 singletons from ATCC BAA-2158 that were absent or highly divergent in the genomes of Spiraeoideaeinfecting strains CFPB 1430 and ATCC 49946 of E. amylovora (10,12). However, genomic sequence comparison of ATCC BAA-2158 with these strains of E. amylovora and the closely related species E. pyrifoliae DSM 12163 T (11), E. tasmaniensis Et1/99 (5), and E. billingiae Eb661 (4) corroborates other analyses (e.g., DNA-DNA hybridization and sequencing of housekeeping genes) that retain ATCC BAA-2158 within the species E. amylovora (3,7).…”
supporting
confidence: 67%
“…The Pla-mediated, wide attack on control of an important hemostatic process in humans, i.e., the fibrinolysis/coagulation balance (32,60,71), represents a considerable difference in pathogenetic potential between the two bacterial species. The omptin Epo also cleaved human PAI-1; this omptin associates with the plant pathogen E. pyrifoliae, which causes pear blight (30), and epo is carried on a mosaic plasmid, pEP36, that is closely related to the virulence plasmid pEA29 of Erwinia amylovora (40). Serpins of mammals and plants share structural features, which include a similar, exposed RCL that is inserted into the catalytic groove of the target proteinases (17).…”
Section: Discussionmentioning
confidence: 99%
“…Our ongoing research (J. Haiko, unpublished) has shown that Epo is a very poor plasminogen activator, and hence we prefer the name Epo (Erwinia pyrifoliae omptin) instead of PlaA, introduced by McGhee et al (40).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids appear to be a major factor influencing the pan-genome of E. amylovora. However, although several plasmids of different sizes have been detected in isolates of this species (Chiou and Jones 1991;Foster et al 2004;Laurent et al 1989;McGhee et al 2002;Steinberger et al 1990), the knowledge on this extra-chromosomal material is limited to few strains and plasmids.…”
Section: Erwinia Amylovora Genomicsmentioning
confidence: 99%